2020
DOI: 10.1108/jima-03-2020-0070
|View full text |Cite
|
Sign up to set email alerts
|

“Do knowledge, perceived usefulness of halal label and religiosity affect attitude and intention to buy halal-labeled detergent?”

Abstract: Purpose Despite the high research interest regarding Halal products, most studies on Halal products focused on food and cosmetics. This study aims to examine the factors that affect the attitude and purchase intention of non-food Halal products in a limited context of detergent products. This study is derived from the theory of reasoned action. It incorporates knowledge, religiosity and perceived usefulness of Halal label as antecedents of attitude. Design/methodology/approach This study applied a self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 63 publications
2
56
1
8
Order By: Relevance
“…Similarly, the behavioral beliefs determine the consequence of particular behavior. Past studies results revealed that making strong attitude of an individual for consulting food label at point of purchase play significant role in selection of healthy packaged food products (Rizkitysha & Hananto, 2020). Hence forth, the strength of attitude is directly proportion to the strong intention and strong actual behavior.…”
Section: Food Label Reading Attitude and Healthy Packaged Food Intentionmentioning
confidence: 99%
“…Similarly, the behavioral beliefs determine the consequence of particular behavior. Past studies results revealed that making strong attitude of an individual for consulting food label at point of purchase play significant role in selection of healthy packaged food products (Rizkitysha & Hananto, 2020). Hence forth, the strength of attitude is directly proportion to the strong intention and strong actual behavior.…”
Section: Food Label Reading Attitude and Healthy Packaged Food Intentionmentioning
confidence: 99%
“…Berdasarkan penelitian terdahulu (Muhamad dkk., 2017;Chen, 2009;Tuhin dkk., 2020;Rizkitysha & Hananto, 2020) yang meneliti tentang makanan, kosmetik, dan deterjen yang dilakukan di negara Malaysia, Brunei, Thailand dengan menggunakan variabel religiusitas, gaya hidup, sikap dan niat pembelian. Namun belum ada yang meneliti tentang produk Wardah di Jakarta dengan menggabungkan seluruh variabel tersebut dalam satu penelitian, sehingga penelitian ini dilakukan agar dapat mengetahui seberapa besar pengaruh dan hubungan antara religiusitas, gaya hidup, dan sikap konsumen yang akan meningkatkan niat pembelian pada produk Wardah.…”
Section: Pendahuluan Latar Belakangunclassified
“…Dalam penelitian Muhamad dkk. (2017) yang meneliti tentang makanan dalam kemasan, dan Rizkitysha & Hananto (2020) tentang deterjen yang berlebel halal, serta penelitian yang dilakukan oleh Memon dkk. (2020) di Pakistan yang memiliki hasil bahwa religiusitas memiliki pengaruh positif terhadap niat pembelian.…”
Section: Kaitan Antar Variabel Religiusitas Gaya Hidup Sikap Dan Niat Pembelianunclassified
“…Tabel 1 meringkas penelitian yang berkaitan dengan produk halal dalam tujuh tahun terakhir (2015)(2016)(2017)(2018)(2019)(2020)(2021). Penelitian tersebut mencakup produk makanan (Abd Rahman et al, 2015;Ayyub, 2015;Billah et al, 2020;Nurhayati & Hendar, 2019) dan non-makanan (Briliana & Mursito, 2017;Mohd Suki & Mohd Suki, 2018;Rizkitysha & Hananto, 2020). Tabel 1 menunjukkan bahwa eksplorasi pengetahuan produk halal konsumen Muslim Indonesia belum menjadi topik penelitian sebelumnya.…”
Section: Pengetahuan Produk Halalunclassified